MRI based morphometry of caudate nucleus in normal persons - Abedelahi, Ali; Hasanzadeh, Hadi (Archives of Advances in Biosciences, 2013)
Because of continuous changing of anatomy, function and metabolism of the human brain, age- related change is a major risk factor in most prevalent neurodegenerative diseases, including Parkinsons and Huntingtons disease. Therefore, knowing patterns of age-related atrophy of brain tissue can identify causes and possible role of diseases in decreasing brain function with age. The aim of this study was to determine the age, sex, and hemispheric differences in volume of the human neostriatum (striatum) nucleus in right-handed healthy humans. This study was performed on 120 normal human subjects (60 males, 60 females) 15–65 years old that was divided into young (<40 years) and old (≥40 years) groups. The sectional brain images obtained via magnetic resonance imaging (MRI) was analyzed and processed using the Image-J software and the caudate volume was calculated using the Cavalieri’s principle. The analyses revealed bilateral age-related changes in the caudate volume of both sexes and the caudate nucleus was significantly smaller in older than younger subjects (P<0.001). There were statistically significant volume differences between males and females (P<0.05) and there was a significant negative correlation between age and volume of the caudate nucleus. Our results provide useful baseline data on age and gender-related changes of caudate volume in neurodegenerative diseases such as Parkinsons and Huntingtons, which has the potential to diagnose neurodegenerative disease before the appearance of typical clinical symptoms.